Does a low-income urban population practise healthy dietary habits? - Azizan, Nurul Ain; Thangiah, Nithiah; Tin, Tin Su; Majid, Hazreen Abdul (Oxford University Press, 2018)
Background: The purpose of this study was to identify the unhealthy dietary habits and practices in a lowincome community in an urban area and determine the associated factors. Methods: A cross-sectional survey was conducted in a low-income housing area in Kuala Lumpur, Malaysia. Data were collected using a questionnaire via face-to-face interviews by trained enumerators in order to obtain details on sociodemographic characteristics and dietary practices. Results: Descriptive statistics showed that 86.7% of the respondents in the low-income community consumed fruit and vegetables less than five times per day, 11.7% consumed carbonated and sweetened drinks more than twice per day and about 25% consumed fast food more than four times per month. In total, 65.2% (n=945) did not have healthy dietary practices. Binary logistic regression showed that age, education and ethnicity were significant predictors of unhealthy dietary practices among the low-income community. Those in the 30-59 years age group had higher odds (odds ratio 1.65, p=0.04) of practising an unhealthy diet as compared with those older than 60 years of age. Conclusion: Unhealthy dietary practices were found to be common among the low-income group living in an urban area. Healthy lifestyle intervention should be highlighted so that it can be adopted in the low-income group.